The Alienation Experienced by Bruno & Shmuel in The Boy in the Striped Pajamas by John Boyne - Anshori, Hafiz (English Literature Study Program, 2023)
Alienation is described as encompassing individual psychological states and types of social relationships. In the context of this study, individuals experience profound feelings of disconnection and estrangement (Kalekin-Fishman, 1998). The objective of this research was to elucidate the diverse causes of alienation depicted in the novel